Getting Serious About Diversity: Reaching Out to Historically Black Colleges and Universities - LaRae M. Donnellan (Journal of Applied Communications, 2004)
In 2002, surveys were sent to heads of agricultural communications offices at land-grant universities (LGUs) and to journalism placement officers at historically black colleges and universities (HBCUs). Research questions focused on the hiring practices at the LGUs and the placement activities at the HBCUs. Although the LGU offices professed a desire for a diverse workforce, respondents indicated that about 88 percent of their employees and 65 percent of their student workers were Caucasian. Three quarters said they posted job notices on their university’s personnel lists and in their local newspapers. Only nine of 40 said they sent notices to journalism schools at 1890 (historically black) LGUs, and only seven sent them to journalism schools at HBCUs. Thirty-five respondents said they used interns, although 30 of those only hired students at their respective universities. Nine of 12 HBCU placement officers said they had never seen a job or internship notice from a LGU. They preferred receiving job or internship notices by surface mail or email. Two thirds of the internships held by their students were unpaid. Although most internships were near campus, respondents said students often seek summer internships near their homes. For LGU communications offices to increase the number of minorities on staff, these offices need to send notices for jobs and internships (especially for summer) directly to minority-serving institutions. Agricultural communications offices at LGUs and minority-serving institutions should work together to develop a system for increasing the number of minority applicants in the LGU pipeline.